The psychology of elite cycling: a systematic review - Spindler, D. J.; Allen, M. S.; Vella, S. A.; Swann, C. (Journal of Sports Sciences, 2018)
This systematic review sought to synthesise what is currently known about the psychology of elite cycling. Nine electronic databases were searched in March 2017 for studies reporting an empirical test of any psychological construct in an elite cycling sample. Fourteen studies (total n = 427) met inclusion criteria. Eight studies were coded as having high risk of bias. Themes extracted included mood, anxiety, self-confidence, pain, and cognitive function. Few studies had similar objectives meaning that in many instances findings could not be synthesised in a meaningful way. Nevertheless, there was some cross-study evidence that elite cyclists have more positive mood states (relative to normative scores), pre-race anxiety impairs performance (among male cyclists), and associative strategies are perceived as helpful for pain management. Among single studies coded as having low risk of bias, evidence suggests that implicit beliefs affect decision making performance, elite cyclists are less susceptible to mental fatigue (than non-elite cyclists), and better leadership skills relates to greater social labouring. Limitations include non-standardisation of measures, lack of follow-up data, small sample sizes, and overall poor research quality. The findings of this systematic review might be used to inform research and theory development on the psychology of elite endurance cycling.